2017
DOI: 10.1007/s11418-017-1114-5
|View full text |Cite|
|
Sign up to set email alerts
|

Resin glycosides from Convolvulaceae plants

Abstract: Resin glycosides are well known as purgative ingredients, which are characteristic of certain crude drugs such as Mexican Scammony Radix, Orizabae Tuber, and Jalapae Tuber, all of which originate from Convolvulaceae plants. Depending on their solubility in ether, these are roughly classified into two groups-jalapin (soluble) and convolvulin (insoluble). Almost all jalapins hitherto isolated and characterized had common intramolecular macrocyclic ester structures. These are composed of 1 mol of oligoglycoside o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 58 publications
(77 reference statements)
1
31
0
Order By: Relevance
“…The remaining glycosidic acid fraction was treated with trimethylsilyldiazomethane-hexane and then subjected to ODS column chromatography and HPLC using πNAP and ODS columns to yield four methyl esters (7-10) of glycosidic acids, among which 9 was identified as muricatic acid C methyl ester, based on its reported physical and 1 H-and 13 C-NMR spectral data. 3) Upon alkaline hydrolysis, 7-10 gave the corresponding free glycosidic acids (7a-10a). Compounds 7a and 8a were identified as muricatic acids A and B, respectively, based on their NMR spectral data 1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining glycosidic acid fraction was treated with trimethylsilyldiazomethane-hexane and then subjected to ODS column chromatography and HPLC using πNAP and ODS columns to yield four methyl esters (7-10) of glycosidic acids, among which 9 was identified as muricatic acid C methyl ester, based on its reported physical and 1 H-and 13 C-NMR spectral data. 3) Upon alkaline hydrolysis, 7-10 gave the corresponding free glycosidic acids (7a-10a). Compounds 7a and 8a were identified as muricatic acids A and B, respectively, based on their NMR spectral data 1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1) Noda et al reported that alkaline hydrolysis of the crude resin glycoside fraction of the seeds of I. muricata yielded three organic acids, namely, isobutyric, 2S-methylbutyric, and 2R-methyl-3R-hydroxybutyric (2R,3R-nilic) acid; and a glycosidic acid fraction composed of L-rhamnose, D-fucose, D-quinovose, and 11R-hydroxyhexadecanoic (jalapinolic) acid, 1) whose absolute configuration was later corrected as S. 2) They also discussed the isolation and structural elucidation of three glycosidic acids, namely, muricatic acids A-C. 1,3) Eight genuine resin glycosides having macrolactone structures (jalapins), 4) namely, muricatins I-VIII were also reported. 3,5) In a previous paper, we reported the isolation and structural elucidation of a new type of resin glycoside, namely, muricatin IX, from the seeds of I. muricata, in which an organic acid connects the sugar moiety and the aglycone moiety to form a macrocyclic ester ring. 6) Recently, Wang et al reported the isolation and structural elucidation of nine jalapins, namely, calonyctins B-J, from the seeds of I. muricata, four of which were structurally similar to muricatin IX.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, herbal plants have received increasing attention as new therapeutic drugs for the treatment of constipation and related diseases [21, 22]. In order to develop drugs for the treatment of constipation, we studied the therapeutic effect of Pharbitis Semen (Convolvulaceae), which is used as a traditional stimulant laxative herb in Korea, China, and Japan [23]. It is reported that resin glycosides are the material basis that account for the purgative action of convolvulaceous species as traditional purgative medicine throughout the world [8].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have used a whole purple sweet potato to determine anthocyanins and other phenolic compounds [ 23 , 24 ]. When a purple sweet potato is cut horizontally, a white round band divides the outer and inner layers; the outer layer is often discarded during processing [ 25 ]. However, the outer layer is a possible commercial source of phenolics, especially anthocyanin pigments.…”
Section: Introductionmentioning
confidence: 99%